1982
DOI: 10.1083/jcb.95.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary rabbit kidney cultures that express proximal tubule functions in a hormonally defined medium.

Abstract: Primary cultures of rabbit-kidney epithelial cells derived from purified proximal tubules were maintained without fibroblast overgrowth in a hormone-supplemented serumfree medium (Medium RK-1). A hormone-deletion study indicated that the primary cultures derived from purified rabbit proximal tubules required all of the three supplements in Medium RK-1 (insulin, transferrin, and hydrocortisone) for optimal growth but did not grow in response to EGF and Ta. In contrast, the epithelial cells in primary cultures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
226
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(241 citation statements)
references
References 40 publications
15
226
0
Order By: Relevance
“…PTCs have a number of differentiated typical functions of the renal proximal tubules, including a polarized morphology, as well as a distinctive proximal tubule transport and hormone response (9,17). It was previously reported that the ATPincreased cell proliferation in primary cultured PTCs is consistent with the results obtained from intact renal tissue (23,24).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…PTCs have a number of differentiated typical functions of the renal proximal tubules, including a polarized morphology, as well as a distinctive proximal tubule transport and hormone response (9,17). It was previously reported that the ATPincreased cell proliferation in primary cultured PTCs is consistent with the results obtained from intact renal tissue (23,24).…”
supporting
confidence: 81%
“…The primary rabbit PTC cultures were prepared by the method reported by Chung et al (9). PTCs were grown in a DMEM-F-12 medium (GIBCO-BRL, Gaithersburg, MD) containing 15 mM HEPES and 20 mM sodium bicarbonate (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit proximal tubular cells were isolated by the method of Brendel & Meezan (1975) and prepared for cultures according to the method of Chung et al (1982) with some modifications from adult male New Zealand white rabbits as described previously (Kim et al 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Renal proximal tubule cells were isolated from the kidneys of young male rabbits and placed in primary culture using an approach similar to that described (6)(7)(8)(9) (5 ,ug/ml), 50 nM hydrocortisone, transferrin (35 pug/ml), 29 nM sodium selenite, 20 AM ethanolamine, 1.5 mM L-glutamine, penicillin (100 units/ml), and streptomycin (100 ,ug/ml). Fetal bovine serum was added to 3% (vol/vol) to the culture medium for the first 3 days to allow better cell attachment.…”
mentioning
confidence: 99%